High-resolution diffusion-weighted imaging for the separation of benign from malignant BI-RADS 4/5 lesions found on breast MRI at 3T - Wisner, Dorota J.; Rogers, Nathan; Deshpande, Vibhas S.; Newitt, David N.; Laub, Gerhard A.; Porter, David A.; Kornak, John; Joe, Bonnie N.; Hylton, Nola M. (Journal of magnetic resonance imaging, 2014)
Purpose To determine whether readout‐segmented echo‐planar diffusion imaging (RESOLVE) improves separation of malignant versus benign lesions compared to standard single‐shot echo‐planar imaging (ss‐EPI) on BI‐RADS 4/5 lesions detected on breast magnetic resonance imaging (MRI). Materials and Methods Consecutive 3T breast MRI studies with BI‐RADS 4/5 designation and subsequent biopsy or benign mastectomy were retrospectively identified. Freehand regions of interest (ROIs) were drawn on lesions and also on normal background fibroglandular tissue for comparison. Lesion‐to‐background contrast was evaluated by normalizing signal intensity of the lesion ROI by the normal background tissue ROI at b = 800. Statistical analysis used the Mann–Whitney/Wilcoxon rank‐sum test for unpaired and Wilcoxon signed‐rank for paired comparisons. Results Of 38 lesions in 32 patients, 10 were malignant. Lesion‐to‐background contrast was higher on RESOLVE than ss‐EPI (1.80 ± 0.71 vs. 1.62 ± 0.63, P = 0.03). Mean apparent diffusion coefficient (ADC) was the same or lower on RESOLVE than ss‐EPI, and this effect was largest in malignant lesions (RESOLVE 0.90 ± 0.13; ss‐EPI 1.00 ± 0.13; median difference −0.10 (95% confidence interval [CI]: −0.17, −0.02) × 10−3mm2/sec; P = 0.014). By either diffusion method, there was a statistically significant difference between benign and malignant mean ADC (P < 0.001). Conclusion Increased lesion‐to‐background contrast and improved separation of benign from malignant lesions by RESOLVE compared to standard diffusion suggests that RESOLVE may show promise as an adjunct to clinical breast MRI. J. Magn. Reson. Imaging 2014;40:674–681. © 2013 Wiley Periodicals, Inc.